2020
DOI: 10.18332/popmed/128600
|View full text |Cite
|
Sign up to set email alerts
|

Differences in HIV treatment experiences, perceptions, and behaviors by gender and sexual orientation in 25 middle-income and high-income countries: Findings from the 2019 Positive Perspectives Survey

Abstract: INTRODUCTION Understanding differences in knowledge and behaviors among men who have sex with men (MSM), men who have sex with women (MSW), and women, is critical to tailor HIV treatment. We investigated these differences among an international sample of people living with HIV (PLHIV) in 25 countries. METHODS Data came from the 2019 Positive Perspectives Study, an online convenience sample of PLHIV in 25 middleand high-income countries. Participants were categorized as MSM (n=1018), MSW (n=479), or women (n=69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Another key difference identified in the case reports presented in this paper was the greater health literacy of the gay male as compared to the heterosexual female and male. This finding is mirrored by other studies that report MSM can demonstrate greater understanding of their medications, greater perceived comfort in discussing their challenges with medical professionals and greater overall involvement in their care [7].…”
Section: Access To Medical Servicessupporting
confidence: 65%
See 3 more Smart Citations
“…Another key difference identified in the case reports presented in this paper was the greater health literacy of the gay male as compared to the heterosexual female and male. This finding is mirrored by other studies that report MSM can demonstrate greater understanding of their medications, greater perceived comfort in discussing their challenges with medical professionals and greater overall involvement in their care [7].…”
Section: Access To Medical Servicessupporting
confidence: 65%
“…In Australia, the focus on HIV as predominately affecting MSM has meant heterosexual females and heterosexual males may fall outside the routine screening, be less likely to share their HIV status with healthcare providers outside of their main HIV medical service, and, therefore, miss the opportunity for timely and regular interventions [7,15]. A longitudinal study conducted in middle-income and high-income countries identified higher rates of non-retention in care among heterosexual males, opening the door for poorer virus control and potentially poorer overall health [7]. Findings from this international study also identified more differences existed between heterosexual males and MSM than between heterosexual males and women in a number of health-related outcomes.…”
Section: Access To Medical Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2019 Positive Perspectives Study was conducted in 25 countries among 2389 PLHIV aged 18–84 years [ 7 9 , 13 16 ]. All participants were on ART at the time of the survey and provided informed consent.…”
Section: Methodsmentioning
confidence: 99%